Perancangan User Experience Aplikasi Parenting Dengan Menggunakan Pendekatan Human-Centered Design - David Panta Palado S.; Hanifah Muslimah Az-Zahra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
It's important to find out information related to early childhood development.Early childhood development is the responsibility of parents as a family that is the beginning in the development of children before entering a higher level, namely school. However, parents' knowledge and experience of information on the development of young children is very minimal. These problems the authors found in parents who are actively conducting care and supervision of early childhood in conducting interviews. Based on existing and valid problems, it is necessary to do a new innovation solution that can improve the experience of parents in solving problems and the needs of prospective users, namely parents in providing information and activities of early childhood. To realize and enhance parents experience of innovations and new solutions that have good value and usability value in accordance with the problems of parents, user experience design is needed. The design of this user experience uses the human-centered design (HCD) method. The human-centered design method is an interactive approach that aims to make the system usable and useful by focusing on the needs of users by increasing aspects of user effectiveness and efficiency and satisfaction. The design of user experience parenting applications with human-centered design methods results in the design of user requirements, interaction designs, lowfidelity interface designs, screenflow designs, high-fidelity designs, and interactive prototypes. The results of the design evaluation using Monroy's heuristic evaluation method produced 18 problem findings on 5 heuristic principles from 9 principles and produced information that the highest average severity rating was found in the heuristic make System Status Visible (MA01) principle, with the most problems found in heuristic principles have the app remember important stuff and not the user (MA06) as many as 7 problem findings with a minor rating severity level. Thus the results of the evaluation produce aesthetic design and minimal design so that prospective users (parents) are comfortable when using the application. The design results also produce a consistent design because the use of location, coloring and shape both menus and icons remain on the design system.